Práticas de leitura na formação inicial de professores e professoras de física: um estudo no Instituto Federal de Educação, Ciência e Tecnologia de Sergipe - Lima, Deivesson de Sousa (2020)
This research has as general objective to analyze the reading practices intheinitialformation process of Physics teachers, of the Federal Institute of Education, ScienceandTechnology of Sergipe (IFS), Campus Lagarto, with a view to the identificationof theinterrelationships between the profile licensee reader and reader training. It was assumedthat reading is a process of understanding the world that involves essential andsingularcharacteristics of individuals, configuring itself as a potentializing element for the trainingofreaders in undergraduate courses. It was noticed that the spaces of initial teacher training,regardless of the area, are crucial to promote learning with meanings and senses, as well asthe appropriation of disciplinary and curricular knowledge and knowledge, reinforcing,among them, reading and its practices. It was a theoretical-empirical investigation, ofaqualitative nature, which is supported by the movement of thesis-antithesis-synthesisofthedialectic. The subjects were students enrolled in the 2019.2 academic period, in thesubjectsof the Pedagogical Axis of the Physics Degree Course at IFS, who had their admissionthrough the Unified Selection System (SISU), and participated in the Project 'ReflectiveAcademic Literacy: working speech, reading and writing in the student's language'.Collaborated as referents for the discussions Koch and Elias (2008), Kleiman (1989; 2001),Cagliari (2003), data from the magazine Retratos da Leitura no Brasil (2003; 2008; 2012;2016), Silva and Silva (2016), Vasconcellos (2011), André (2001), Anastasiou(2005),Konder (2008), Barros and Gasparin (2012), Lakatos and Marconi (2011), ProdanovandFreitas (2013), Vergara (2013), Ludwuig (2014) , IFS (2014, 2015, 2017), Brazil (1996;1998; 2002; 2014; 2019), Moraes and Galiazzi (2006; 2007; 2011; 2016) amongotherauthors. As for the instruments, questionnaires (online), formative reading activitiesandreflective memorial production were used. With the information collected, workedinthelight of the discursive textual analysis, considering the phases of deconstruction/unitarization, categorization and construction of the metatext, three emerging categoriesofreaders were identified: formed reader, semi-formed reader and reader information,concluding with the need to foster actions that corroborate for the improvement of readingand its achievements, in educational institutions.